Plasma matrix metalloproteinases and tissue inhibitors of metalloproteinases explored in relation to the severity and progression of diabetic retinopathy in patients with type 1 diabetes: baseline and prospective analyses - Sven Hector; Hans Olav Thulesius; Mona Landin-Olsson; Magnus Hillman; Eva Olga Melin; Maria Thunander (BMJ Open Ophthalmology)
Aims To explore whether circulating matrix metalloproteinase-2 (MMP-2), MMP-9, MMP-9/neutrophil gelatinase-associated lipocalin, MMP-9/tissue inhibitor of metalloproteinase-1 (TIMP-1), MMP-14, TIMP-2 and TIMP-3 were associated with the severity and progression of diabetic retinopathy (DR) in patients with type 1 diabetes (T1D).Methods Baseline and prospective analyses were conducted over a period of 10.5 person-years. In 2009, recruitment and biochemical analyses (MMPs, TIMPs, glycated haemoglobin (HbA1c), serum creatinine, macroalbuminuria) were performed. Fundus photography, performed at baseline and at follow-up in accordance with the regional screening programme, was compared after being categorised according to the International Clinical Diabetic Retinopathy Disease Severity Scale. ‘DR progression at least one leve’ was calculated. High MMP-2 was defined as ≥178 ng/mL (≥75th percentile) and high TIMP-2 as ≥205 ng/mL (≥75th percentile). DR was dichotomised as ‘at least moderate DR’ or ‘no/mild DR’.Results The study included 267 participants, 57% of whom were men. At baseline, the prevalence of high MMP-2 (p=0.001) and high TIMP-2 (p=0.008) increased with the severity of DR. ‘At least moderate DR’ (adjusted OR (AOR) 2.4, p=0.008) and macroalbuminuria (AOR 3.6, p=0.025) were independently associated with high MMP-2. ‘At least moderate DR’ (AOR 2.3, p=0.009) and macroalbuminuria (3.4, p=0.031) were independently associated with high TIMP-2. DR progression occurred in 101 (46%) patients (p<0.001). HbA1c≥53 mmol/mol was associated with the progression of DR (crude OR 3.8, p=0.001). No other MMPs or TIMPs were linked to the severity or the progression of DR.Conclusions High levels of MMP-2 and TIMP-2 indicated more severe DR or diabetic nephropathy. Only HbA1c was associated with the progression of DR in 267 patients with T1D.